ВЫБОР ТЕМЫ, СЮЖЕТ И ТИПИЧНОСТЬ В СОВРЕМЕННОЙ АЗЕРБАЙДЖАНСКОЙ ЛИТЕРАТУРЕ. (Eurasian Journal of Philology Science and Education, 2015)
Speaking about creative qualities of the modernAzerbaijan literature first of all it is necessary to underlineproblems of a choice of a theme, a plot and typicalness.Because it is impossible to stand aside from understandingof the given problem in the decision of creative problems. Inother words, would be inexpedient to estimate the creativeparties of any art value, having ignored his theme, a plot andtypicalness